Friedrich Schlegels Gedanken über Polen - Grzywacz, Małgorzata (Studia Germanica Posnaniensia, 2018)
Frederick Schlegel's, the leading thinker's of German Romanticism, interest in Poland, dates back to 1794, when he favourably estimated the „Kosciuszko“ Insurrection. In actuality, the interest in Polish affairs was the cause of his conversion into Catholicism in 1808. Jn Poles he saw a Catholic nation belonging to a Christian community. The opinion of history of the Polish nation included in „The Lectures about modem history“ (Vienna 1811), seems interesting. He considers Louis d'Anjou to be the greatest Polish King, whose biggest contributions to Polish history were his uncanny abilities as a lawgiver. This perspective probably results from his dealings with Hungary and its history, as well as sheer ignorance of Poland and Poles. His opinion of Polish language and literature as exemplified during his „Lectures on the History of Literature Past and Present“ (Vienna 1812) is similar to his previous opinion. This ignorance does not diminish his sympathy for Poland, as one can see by boiling through his private memoirs (the so-called Fragments) which were published posthumously.